Cryptosporidium spp. during chemotherapy: a cross-sectional study of 94 patients with malignant solid tumor - Mehmet Karabey (King Faisal Specialist Hospital and Research Centre, 2021)
BACKGROUND: Cryptosporidium spp. is a protozoan parasite that infects many vertebrate animals, including humans. Since Cryptosporidium spp. can cause chronic life-threatening diarrhea and severe malabsorption in immunocompromised patients, we investigated the prevalence of this parasite among patients undergoing chemotherapy for malignant solid tumors. OBJECTIVE: Investigate the prevalence of Cryptosporidium spp. in stool samples. DESIGN: Cross-sectional. SETTING: Tertiary care. PATIENTS AND METHODS: Stool samples were collected from adult patients with malignant solid tumors receiving chemotherapy and diarrhea. Cryptosporidium spp. prevalence was determined using Ziehl–Neelsen staining, ELISA, and real-time PCR targeting of the COWP gene. MAIN OUTCOME MEASURE: The prevalence of Cryptosporidium spp. in patients undergoing chemotherapy for malignant solid tumors. SAMPLE SIZE: 94 RESULTS: The prevalence was 2.1% (2/94), 5.3% (5/94), and 5.3% (5/94) as detected by Ziehl–Neelsen staining, real-time PCR and ELISA, respectively. The prevalence reached 8.5% (8/94) using all results obtained from the three methods. Among eight positive stool samples, four were positive by at least two different methods (Ziehl–Neelsen staining-ELISA or ELISA-real-time PCR) whereas the remaining four were positive by either ELISA or real-time PCR. CONCLUSION: These findings show the risk of cryptosporidiosis in cancer patients and the necessity to use at least two diagnostic methods during the diagnosis of cryptosporidiosis to reach more accurate and trustworthy results. LIMITATIONS: Further studies with a larger sample size are recommended. CONFLICT OF INTEREST: None.